Electrophoretic deposition of coatings for local delivery of therapeutic agents - Cheng, Xian; Liu, Yanping; Liu, Ousheng; Lu, Yanqin; Liao, Zhengwei; Hadzhieva, Zoya; Chen, Lili; Leeuwenburgh, Sander G.C.; Boccaccini, Aldo R.; Yang, Fang (Progress in Materials Science, 2023)
Electrophoretic deposition (EPD) is an effective technique to construct coatings onto the surface of medical devices. These coatings can act as reservoirs for local delivery of therapeutic agents, including metal ions and metal-free drugs. This manuscript presents a comprehensive overview of the fundamentals and application of EPD coatings for local delivery of therapeutic agents, with a specific focus on the mechanism and control over loading and release of therapeutic agents. After a brief introduction of the EPD coating process, the matrices that are most commonly deposited using EPD for drug delivery purposes are summarized including the mechanism of their deposition without additives and co-deposition with additives. Subsequently, three strategies towards loading therapeutic agents are discussed, including i) co-deposition of therapeutic agents with coating matrices, ii) pre-loading therapeutic agents into microcarriers, and iii) post-loading therapeutic agents into prepared coatings. Furthermore, factors influencing loading (e.g., EPD processing parameters and additives) are identified. Subsequently, the release mechanisms as well as the influence of both intrinsic (e.g., additives, layered structures, building blocks, and microcarrier properties) and extrinsic processing parameters (e.g., pH, electric, magnetic and photothermal stimuli) used to tune the release kinetics are presented. Additionally, the applications of therapeutic agent loaded EPD coatings are summarized. Finally, the remaining challenges and future perspectives related to the use of EPD coatings for drug delivery purposes are reviewed.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Coatings; Drug loading; Drug release; Electrophoretic deposition; Therapeutic metal ions